PENGATURAN PENYELESAIAN PERSELISIHAN HASIL PEMILIHAN KEPALA DESA DI INDONESIA - Deki Azhari; Syamsir Syamsir; Firmansyah Putra (Universitas Jambi, Fakultas Hukum, 2022)
AbstrakThis study aims to analyze the arrangements regarding the settlement of disputes over the results of the Village Head Election. The Village Head Election is a forum to accommodate the aspirations of the village community in terms of politics as well as a means of changing leadership in the village government, but in the process there are often disputes in the implementation of village head elections caused by various kinds of fraud that occur such as the existence of prospective candidates who violate the requirements, process election and vote counting that is not honest and fair and the election committee acts unfairly and favors one of the candidates, and others. The election of village heads and their settlement has been regulated in UU No.6 Tahun 2014 concerning Villages which gives authority to the Regent/Mayor to settle disputes over the election of the village head, while the position of Regent/Mayor is a political position and is also included in the executive group, which should every disputes or disputes are resolved by the judiciary. Actually there is the most relevant solution to be applied in resolving disputes over the results of the village head election, namely through the